Analisis Efektivitas Pengelolaan Dana Desa Untuk Meningkatkan Pembangunan Ekonomi Lokal di Desa Klepu Kecamatan Pringapus Kabupaten Semarang - Harefa, Wilman Hasrat; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article aims to analyze the effectiveness of village fund management in improving local economic development in Klepu Village, Pringapus District, Semarang Regency. The study focuses on how effectively this policy has promoted local potential–based economic growth and the factors influencing it. The analysis is based on the concepts of good governance and endogenous local economic development. Data were collected through in-depth interviews, participatory observation, and document studies involving village officials, the Village Consultative Body (BPD), micro-entrepreneurs, and community leaders, then analyzed qualitatively using the interactive model of Miles and Huberman. The results show that the governance of village funds in Klepu has been implemented in a participatory and transparent manner through deliberation mechanisms, contributing to the improvement of productive infrastructure, empowerment of micro-enterprises, and expansion of employment opportunities. However, its effectiveness remains suboptimal due to limited administrative capacity, low community participation in supervision, and the underperformance of village-owned enterprises (BUMDes). This study concludes that improving management effectiveness requires strengthening human resource capacity, enhancing public transparency, and revitalizing local economic institutions to ensure sustainable local economic development.